Peptidomics in Food - Dalabasmaz, Sevim; Pischetsrieder, Monika (Comprehensive Foodomics, 2020)
Peptides are important food components with bioactive properties (including, e.g., antimicrobial, antioxidative, ACE-inhibitory or anticariogenic effects) and technological function. By now, targeted and untargeted mass spectrometry, mainly MALDI-TOF-MS and LC–ESI-high resolution MS/MS, allow for the comprehensive analysis of the peptide composition in food. Food peptidomics or food peptide profiling are crucial techniques to identify and quantify bioactive peptides in food and to understand the influence of peptides on food quality. Bioinformatic tools facilitate linking peptide structures and functions. Additionally, peptide profiles can complement the analytical toolbox to assure food authenticit
Keywords: ACE-Inhibitory activity; Antimicrobial activity; Antioxidative activity; Bioactive peptides; Food authentication; LC–MS/MS; MALDI-TOF-MS; Milk products; Peptide databases; Peptide profile; Peptidomics; Phosphopeptides; Quantification. Targeted analysis Untargeted analysis